2012
DOI: 10.1517/17425255.2012.685237
|View full text |Cite
|
Sign up to set email alerts
|

Role of CAR and PXR in xenobiotic sensing and metabolism

Abstract: Introduction The xenobiotic detoxification system, which protects the human body from external chemicals, comprises drug-metabolizing enzymes and transporters whose expressions are regulated by pregnane X receptor (PXR) and the constitutive androstane receptor (CAR). The progress made in a large number of recent studies calls for a timely review to summarize and highlight these key discoveries. Areas covered This review summarizes recent advances in elucidating the roles of PXR and CAR in the xenobiotic deto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
192
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(197 citation statements)
references
References 131 publications
(140 reference statements)
2
192
1
2
Order By: Relevance
“…Gene ontology (GO) enrichment analysis based on a mean log P value indicates that the GO terms such as drug metabolism, lipid metabolism, and hormone metabolism are significantly overrepresented among genes downregulated by NeoB ( Table 2). Many of the genes involved in these metabolic processes are regulated by transcription factors, including nuclear hormone receptors (46,47). Moreover, the HCV life cycle is known to be modulated by multiple nuclear hormone receptors such as peroxisome proliferator-activated receptor (PPAR), estrogen receptor (ER), and farnesoid X receptor (32,(48)(49)(50), leading us to question whether NeoB affected the function of nuclear hormone receptors that, in turn, modulate HCV replication.…”
Section: Resultsmentioning
confidence: 99%
“…Gene ontology (GO) enrichment analysis based on a mean log P value indicates that the GO terms such as drug metabolism, lipid metabolism, and hormone metabolism are significantly overrepresented among genes downregulated by NeoB ( Table 2). Many of the genes involved in these metabolic processes are regulated by transcription factors, including nuclear hormone receptors (46,47). Moreover, the HCV life cycle is known to be modulated by multiple nuclear hormone receptors such as peroxisome proliferator-activated receptor (PPAR), estrogen receptor (ER), and farnesoid X receptor (32,(48)(49)(50), leading us to question whether NeoB affected the function of nuclear hormone receptors that, in turn, modulate HCV replication.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the mechanisms underlying the downregulation of the CYP3A4 gene, the expression of the CYP3A4 gene was regulated by nuclear receptors, wellestablished xenobiotic sensors capable of binding to various structurally diverse chemicals, such as pregnane X receptor (PXR) (30) and constitutive androstane receptor (CAR) (30,31). Promoter hyper-methylation has been reported to result in repression of CAR and PXR expression, which induces the down-regulation of drug-metabolizing enzymes, including the CYP3A4 gene, in human pluripotent stem cellderived hepatocyte-like cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…Ethical approval for all experimental protocols and study was obtained from the institutional review board at the Shizuoka Cancer Center (Authorization Number: [25][26][27][28][29][30][31][32][33]. Written informed consent was obtained from all patients enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
“…[2] These nuclear receptors recognize endogenous and exogenous ligands and transduce these internal and environmental signals into upregulation or downregulation of target genes, including P450 genes. Experimental studies have revealed numerous ligands of PXR and CAR, such as certain drugs, lipids, bile acids, and hormones.…”
Section: Introductionmentioning
confidence: 99%